2021
DOI: 10.1038/s41598-021-90651-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Apgar scores and long-term cognitive outcomes in individuals with Down syndrome

Abstract: This study examined the contribution of the Apgar score at 1 and 5 min after birth to later cognitive functioning in 168 individuals with Down syndrome who were between 6 and 25 years of age at time of cognitive testing. Our results showed that a lower Apgar score at 1 min was related to a worse performance in later cognitive measures of receptive vocabulary, verbal comprehension and production, visual memory and working memory. Results also showed that a lower Apgar score at 5 min was only related to worse la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Despite this characteristic phenotype, there is considerable variability in the presentation and severity of challenges observed among individuals with DS. This variability is associated with a constellation of environmental and biological factors (del Hoyo et al, 2016 ; del Soriano et al, 2021 ; Karmiloff-Smith et al, 2016 ; Thomas et al, 2020 ). In the study reported here, we examine the association of sex (as assigned at birth, hereafter simply “sex”) with variation in the behavioral phenotype of DS.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this characteristic phenotype, there is considerable variability in the presentation and severity of challenges observed among individuals with DS. This variability is associated with a constellation of environmental and biological factors (del Hoyo et al, 2016 ; del Soriano et al, 2021 ; Karmiloff-Smith et al, 2016 ; Thomas et al, 2020 ). In the study reported here, we examine the association of sex (as assigned at birth, hereafter simply “sex”) with variation in the behavioral phenotype of DS.…”
Section: Introductionmentioning
confidence: 99%
“…First, different characteristics might be grouped in perinatal and neonatal status and development. The APGAR score at 1 min after birth is a measure of the physical condition of a newborn infant that can influence the neonatal development [ 38 ]. Hearing loss has been demonstrated to affect language and cognitive skills development [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apgar score is a common measurement of the immediate health status of infants after delivery, based on skin complexion, heart rate, muscle tone, reflex irritability, and respiration effort. Apgar score has been shown to be associated with cognitive function as well as risk of childhood cancer [ 36 , 37 ]. We obtained information about paternal age at delivery through the Multi-Generation Register [ 32 , 38 ].…”
Section: Methodsmentioning
confidence: 99%